The demise of catalysis, but new functions arise: pseudoenzymes as the phoenixes of the protein world. (1st February 2019) - Jeffery, Constance J.
Abstract : Pseudoenzymes are noncatalytic homologues of enzymes and are found in most enzyme families. Although lacking catalytic activity and sometimes referred to as 'dead' enzymes, they instead resemble phoenixes because the loss of a catalytic function during evolution was associated with the development of vital new functions. They are important in regulating the activity and location of catalytically active homologues, scaffolding the assembly of signaling complexes, and regulating transcription or translation. They are key actors in cell proliferation and differentiation, proteostasis, and many other biochemical pathways and processes. They perform their functions in diverse ways, but many retain some aspects of the function of their catalytically active homologues. In some pseudoenzymes, their functions are very different from other members of their protein families, suggesting some arose from ancient moonlighting proteins during evolution. Much less is known about pseudoenzymes than their catalytically active counterparts, but a growing appreciation of their key roles in many important biochemical processes and signaling pathways has led to increased investigation in recent years. It is clear that there is still much more to learn about the structures, functions, and cellular roles of these phoenix-like proteins.